Identification of IFN-γ-producing T cells as the main mediators of the side effects associated to mouse interleukin-15 sustained exposure - Scala, Marianna Di; Gil-Fariña, Irene (OncoTarget, 2016)
Oncotarget | https://doi.org/10.18632/oncotarget.10264 Marianna Di Scala, Irene Gil-Fariña, Cristina Olagüe, Africa Vales, Luciano Sobrevals, Puri Fortes, David Corbacho, Gloria González-Aseguinolaza